Impact of overweight on the burden of non-communicable diseases in Belgium: the WaIST project. (30th September 2020) - Gorasso, V; De Smedt, D; Vandevijvere, S; De Clercq, E; Van der Heyden, J; Doggen, K; Pelgrims, I; Devleesschauwer, B
Abstract: Issue: Excess weight status is one of the main metabolic risk factors for non-communicable diseases. According to the Belgian health interview survey of 2018, 49.3% of the adult population suffered from overweight. Despite the great national burden, and apart from isolated actions, there is not anymore a comprehensive nutritional and physical activity health plan in Belgium. Consequentially, Belgium requires action-oriented research to support the implementation of evidence-based policies for the prevention of excessive weight gain. Description of the Problem: The WaIST project aims to assess the contribution of excess weight status to the societal impact of non-communicable diseases, disability and multi-morbidity, and to model and compare the potential impact of internationally recommended health policies. The project also aims to support knowledge translation and policy transfer through a close interaction with national decision makers and stakeholders. Results: The disease burden of diabetes, cardiovascular diseases, cancer and musculoskeletal disorders will be estimated in terms of disability-adjusted life years (DALYs) and healthcare expenses from a societal perspective. For this purpose, survey, registry, health insurance, and hospital discharge data will be used. Subsequently, health interventions tackling overweight will be selected considering scientific evidence and stakeholder priorities. Health impact assessments will then be conducted projecting the future impact of the interventions on health outcomes and costs related to excess weight status. Lessons: The use of national data for the computation of the burden of disease provides better estimates for DALYs and costs compared to European or global study results. Moreover, the results of the project will allow to explore the impact of health intervention specific for the Belgian case. Key messages: Considering the burden associated with overweight-related diseases, preventing obesity is important from a public health and financial perspective. Integrating these results into evidence-based policies could provide governments and partners with a key tool for effective health interventions.